Raiding Opportunities and Unemployment - Tranæs, Torben (Journal of Labor Economics, 2001)
This article studies the impact of raiding opportunities in a labor market in which worker abilities differ. Recruiting firms can either raid an elsewhere‐employed worker of known ability by bidding up his wage or go through costly search to find a good worker among the unemployed. In equilibrium, all types of workers experience unemployment, high‐ability workers involuntarily. The raiding opportunities give rise to involuntary unemployment without changing the basic properties of the competitive model and thus suggest new implications of various institutional parameters on unemployment, in particular, unemployment compensation, minimum wages, wage taxation, and search requirements.